Equivalent plate properties of composite corrugated structures using mechanics of structure genome. (January 2021) - Deo, Ankit; Yu, Wenbin
Abstract: Equivalent plate properties are obtained for composite corrugated structures using mechanics of structure genome. The method developed in this paper interprets the unit cell associated with the corrugated structure as an assembly of plates, and the overall strain energy density of the unit cell as a summation of the plate strain energies of these individual plates. Mechanics of structure genome is then applied to drop all higher-order terms and the remaining energy is minimized with respect to the unknown fluctuating functions. This has been done by discretizing the two-dimensional unit cell into one-dimensional frame elements in a finite element description. This allows the handling of structures with different levels of complexities and internal geometry within a general framework. Comparisons have been made with existing work to show the advantage the proposed model offers over existing ones.